Uncovering the Beneficial Role of Limosilactobacillus fermentum E7 Exhibiting Antioxidant Activity in Ameliorating DSS-Induced Ulcerative Colitis in a Murine Model - Hongyan Zhang; Hailing Wang; Yue Li; Yue Leng; Ke Lin; Dayong Ren (Foods)
Background: Ulcerative colitis (UC) is a chronic intestinal disease of growing global concern. Bacteria associated with fermented food or probiotics regulate immune and inflammatory responses, playing a key role in intestinal immune homeostasis. Results: Five probiotics with relatively good antioxidant effects, namely Lactiplantibacillus plantarum H6, Latilactobacillus sakei QC9, Limosilactobacillus fermentum E7, Bacillus subtills D1, and Bacillus licheniformis Q13, were screened out from 30 strains of probiotics through in vitro antioxidant assays. The five probiotics had varying degrees of alleviating effects on UC mice and improved various physiological indicators, such as oxidative stress parameters and histopathological sections. The effects of E7, D1, and Q13 were more pronounced. Furthermore, E7 effectively regulated UC mouse intestinal microbiota composition, increased short-chain fatty acid concentration, and promoted the expression of anti-inflammatory factors, such as interleukin 10 (IL-10), while suppressing that of pro-inflammatory factors, such as interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α). Meanwhile, D1 and Q13 only exhibited partial alleviating effects. Finally, E7 increased the expression of tight junction proteins in colon tissues. Conclusions: E7 showed superior efficacy to other probiotics in alleviating UC, offering novel therapeutic prospects for safer and effective management of UC.